Overlap syndrome in autoimmune thyroid diseases: pathogenesis, diagnosis, and therapeutic approaches - Gendeleka, Grygorii (2026)
The aim of the study is to summarise current data on the pathogenetic mechanisms, clinical manifestations and diagnostic criteria of overlap syndrome in autoimmune thyroid diseases and identify potential biomarkers and directions for improving therapeutic strategies to increase the effectiveness of treatment and predict the course of this pathology. In this regard, a search of publications in PubMed, MEDLINE, and Web of Science databases for the period 1980-2025 was conducted. Clinical cases were described where the transformation occurred under the influence of therapy and spontaneously. It is established that antibodies (TPOAb, TgAb, TSHrAb), thyroid hormone levels, and instrumental methods play a key diagnostic role. Molecular mechanisms are highlighted, in particular epigenetic changes (DNA methylation), microRNA profiles, the role of exosomes and antigenic mimicry of infectious agents, including SARS-CoV-2. It is shown that various mechanisms can cause dominance and switching between autoimmune processes.